Correlations of Brothers' Earnings and Intergenerational Transmission - Paul Bingley; Lorenzo Cappellari (Center for Economic Studies and ifo Institute (CESifo), 2017)
Correlations between parent and child earnings reflect intergenerational mobility and, more broadly, correlations between siblings' earnings reflect shared community and family background. These earnings relationships capture important aspects of relations in socio-economic status more generally. We estimate intergenerational transmission and sibling correlations of life-cycle earnings jointly within a unified framework that nests previous models. Using data on the Danish population of father/first-son/second-son triads we find that intergenerational effects account for on average 72 percent of sibling correlations. This share is higher than all previous studies because we allow for heterogeneous intergenerational transmission between families. Sibling correlations exhibit a U-shape over the working life, consistent with differences in human capital investments between families.
Keywords: D31; J62; 330; sibling correlations; intergenerational transmission